The impact of macroeconomic variables on the performance of selected African stock markets - Epalanga, Amarildo (Department of Finance and Tax, 2022)
This dissertation investigates the impact of macroeconomic variables on the performance of African stock markets, focusing on Egypt, Mauritius, and South Africa during the period 2009– 2019. This dissertation employed the multiple linear regression model and the Granger causality test to ascertain the impact of these factors. For each country, the stock market index was used as a dependant variable while interest rates, inflation rate, money supply, exchange rate, gold price, and oil price were used as independent variables. The results from the country-specific models varied widely from country to country. The heterogeneity of the results may be explained by differences in economic fundamentals between the countries, for example, market depth, market size, and liquidity. The model showed that interest rate, which is inversely related to stock prices, isthe only significant variable in explaining stock prices in Egypt. In Mauritius, it wasfound that only three factors significantly affect stock prices, namely, exchange rate, gold price, and inflation. A depreciation of the Mauritius Rupee to the USD and an increase of the gold prices decrease stock prices in Mauritius, whilst the effect of inflation was found to be positive. In South Africa, results showed that inflation, money supply, and oil prices significantly affect stock prices in the Johannesburg Stock Exchange (JSE). However, unlike for Mauritius (where inflation has a positive impact), in South Africa, its effect is negative. By contrast, money supply and oil prices were found to impact the JSE stock prices positively. Against the backdrop of these findings, this dissertation encourages the governments and policy makers in emerging markets to consider stabilising the macroeconomy to create a conducive environment for stock market development. The Granger causality test reveals that stock prices can be used to predict oil prices in Egypt. In contrast, the South African data suggests no causal relationship between macroeconomic factors and stock prices. Finally, the same test in Mauritius shows that money supply can be used to predict stock prices, and stock prices can be used to forecast gold prices and exchange rates.